Treatment of osteoporosis in men. - Kaufman, J; Reginster, J; Boonen, S; Brandi, M; Cooper, C; Dere, W; Devogelaer, J; Diez-Perez, A; Kanis, J; McCloskey, E; Mitlak, B; Orwoll, E; et al. (2013)
SUMMARY: Aspects of osteoporosis in men, such as screening and identification strategies, definitions of diagnosis and intervention thresholds, and treatment options (both approved and in the pipeline) are discussed. INTRODUCTION: Awareness of osteoporosis in men is improving, although it remains under-diagnosed and under-treated. A European Society for Clinical and Economic Aspects of Osteoporosis and Osteoarthritis (ESCEO) workshop was convened to discuss osteoporosis in men and to provide a report by a panel of experts (the authors). METHODS: A debate with an expert panel on preselected topics was conducted. RESULTS AND CONCLUSIONS: Although additional fracture data are needed to endorse the clinical care of osteoporosis in men, consensus views were reached on diagnostic criteria and intervention thresholds. Empirical data in men display similarities with data acquired in women, despite pathophysiological differences, which may not be clinically relevant. Men should receive treatment at a similar 10-year fracture probability as in women. The design of mixed studies may reduce the lag between comparable treatments for osteoporosis in women becoming available in men.